Stir it up [videorecording (DVD)] - James, Francis; Collins, Rich; Durbin, Scott; Poche, Dave; Smith, Scott (Scott Smitty) (Imagination Movers, 2004)
Collection of music videos, live performances and Blue Suit fun. Dance, hop, slide, jump and drum along with the Movers as they sing about creative games, healthy snacks and learning to sleep through the night.